Examining the impact of knowledge, supervision, and work fatigue on unsafe actions among warehouse workers - Hasanah, Dewi Transmiatun; Ramdan, Iwan Muhamad; Hardianti, Dewi Novita; Lestari, Ida Ayu Indira Dwika (University of Merdeka Malang, 2024)
Unsafe actions are dangerous behaviors that can cause work accidents, resulting in injury or death. Warehouses are high-risk areas for such incidents due to the presence of unsafe actions during work processes. This study aims to explore the relationship between knowledge, supervision, and work fatigue with unsafe actions among warehouse workers at PT Cipta Krida Bahari Samarinda. This quantitative study employs a cross-sectional design, with a sample size of 50 workers using the total sampling technique. The independent variables are knowledge, supervision, and work fatigue, while the dependent variable is unsafe action. Data analysis utilized univariate and bivariate (chi-square) methods. Results indicated that 54 percent of workers engaged in unsafe actions, 60 percent had good knowledge, 56 percent reported good workplace supervision, and 54 percent experienced fatigue. Bivariate analysis showed no significant relationship between knowledge (p=0.203) and work fatigue (p=0.168) with unsafe actions. However, a significant relationship was found between supervision (p=0.019) and unsafe actions. It is recommended that the company enhance supervision practices and enforce strict penalties for violations to minimize unsafe actions among workers.